Comparison of Goal Scoring Patterns in “The Big Five” European Football Leagues - Li, Chunhua; Zhao, Yangqing (Frontiers in Psychology, 2021)
The aim of the present study was to compare goal scoring patterns among the “Big 5” European leagues during the 2009/2010-2018/2019 seasons. A total of 18 pattern dimensions related to the offence method, the shooting situation and the scoring time period were evaluated. Kruskal-Wallis analyses revealed significant pattern differences among the five leagues. The Spanish La Liga showed a greater proportion of goals from throw-ins. The English Premier League had a higher tendency to score from corner kicks. The German Bundesliga had the greatest number of goals from counterattacks and indirect free kicks, and the Italian Serie A had the greatest proportion of penalties. Ligue 1’s scoring ability is weaker than that of the other leagues, especially Bundesliga. The Bundesliga had an overwhelming advantage in goals scored on big chances with assists, while the Premier League had an advantage in goals scored with assists that were not from big chances. However, the differences among the five leagues in the mean goals scored in the last 15 minutes and the goals from elaborate attacks and direct free kicks were not statistically significant. These results provide important insights to coaches and sporting directors for understanding the different goal patterns of each league and allow us to better understand the differences among the leagues.